KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 13 PADANG - Ardiansyah, Aland; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2020)
ABSTRACT This article reveals the contribution of skills reading comprehension to writing skills text exposition grade students VIII SMP Negeri Padang 13. The purpose of this research there are three. First, it describes the skills of reading comprehension grade VIII SMP Negeri 13Padang. Second, it describes the writing skills text eksposition grade VIII SMP Negeri 13Padang. Third, describing the contribution of the intermediate reading comprehension against writing skills text exposition grade VIII SMP Negeri 13 Padang. This research type is quantitative descriptive method. The desain used in this research is the design contribution. This research population is grade VIII SMP Negeri Padang are registered on the 13th school year 2019/2020, i.e. as many as 288 students. The sample in this research are determined by propotional random sampling of 20% of the populations, i.e. 54 students. Research data is a score test results intermediate reading comprehension and score the writing skills test result text exposition. The data obtained through two types of tests i.e. objective tests to measure the skills of reading comprehension text eksposition and performance tests to measure the skills of writing a text eksposition. The results of the research there are three. First, the skills of reading comprehension grade VIII SMP Negeri Padang 13 are on more than enough qualifications (LdC) by the value of the average 75.41. Second, the skills of writing text exposition grade VIII SMP Negeri Padang 13 are on good qualifications (B) with an average of 77.37. Third, there is a contribution of reading skills in the exposition of text to the skills of writing exposition texts of class grade VIII SMP Negeri Padang 13 at 62.77%. Kata kunci: Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Eksposisi.